BlockChain Based Payment Merchant (Global Journal of Computer Science and Technology, 2024)
Blockchain technology has revolutionized various industries and its potential is now being realized in the realm of payment systems This abstract explores the concept of a blockchain-based payment merchant which leverages the decentralized and immutable nature of blockchain to provide secure transparent and efficient transactions Traditional payment systems often suffer from issues such as high transaction fees lengthy settlement times and vulnerabilities to fraud However by utilizing blockchain technology payment merchants can overcome these challenges Blockchain offers a decentralized network where transactions are recorded on a distributed ledger eliminating the need for intermediaries and reducing transaction costs In a blockchain-based payment merchant system merchants and customers interact directly with transactions being recorded as blocks on the blockchain These blocks are linked together through cryptographic algorithms ensuring the integrity and immutability of the transaction history This transparency not only prevents fraud but also enhances trust between parties Overall blockchain-based payment merchants offer numerous advantages including enhanced security transparency reduced costs and faster settlement times However challenges such as scalability regulatory frameworks and user adoption still need to be addressed for widespread implementation As blockchain technology continues to evolve it holds immense potential for transforming the payment landscape and reshaping the way we conduct transactions